1995
DOI: 10.1121/1.412316
|View full text |Cite
|
Sign up to set email alerts
|

Predicting noise-induced sleep disturbance

Abstract: The findings of 21 studies of the effects of noise on sleep were reanalyzed in an effort to develop a quantitative dosage-response relationship. Large and systematic differences in sleep disturbance were observed between the findings of studies conducted in laboratory and in field settings. The influence of noise on sleep was also found to depend on additional factors such as the nature of noise and response metrics, noise source, background noise level, length of study, and sex of test participants. No reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 0 publications
2
58
1
2
Order By: Relevance
“…The observation that the degree of sleep disturbance found in field studies, i.e., after months or years of noise exposure, is usually much lower compared to laboratory studies suggests that habituation continues beyond the periods usually investigated in the laboratory. 35,36 The fact that cardiac arousals habituated within but not across nights suggests either that the mechanisms responsible for habituation across nights differ from those responsible for habituation within nights or that the two mechanisms outlined above contribute differentially to habituation across and within nights, at least for vegetative arousals. The hierarchical nature of the arousal response 37 may explain why habituation across nights was seen for cortical but not for cardiac arousals as, depending on the analysis of the content of the acoustic stimulus, thalamocortical gating may prevent the cortex from being aroused, 38,39 while there may still be a subcortical response independent of information processing of higher central nervous system structures.…”
Section: Event-related Analysismentioning
confidence: 99%
“…The observation that the degree of sleep disturbance found in field studies, i.e., after months or years of noise exposure, is usually much lower compared to laboratory studies suggests that habituation continues beyond the periods usually investigated in the laboratory. 35,36 The fact that cardiac arousals habituated within but not across nights suggests either that the mechanisms responsible for habituation across nights differ from those responsible for habituation within nights or that the two mechanisms outlined above contribute differentially to habituation across and within nights, at least for vegetative arousals. The hierarchical nature of the arousal response 37 may explain why habituation across nights was seen for cortical but not for cardiac arousals as, depending on the analysis of the content of the acoustic stimulus, thalamocortical gating may prevent the cortex from being aroused, 38,39 while there may still be a subcortical response independent of information processing of higher central nervous system structures.…”
Section: Event-related Analysismentioning
confidence: 99%
“…En gjennomgang av mange av studiene frem til midten av 1990-tallet viste til dels store forskjeller i dose-responssammenhenger mellom studier gjennomført i laboratoriet og i en feltsituasjon, dvs. hjemme hos personer som er utsatt for støy om natten (54). Siden man fant at sannsynlighet for virkninger på søvn for et gitt støynivå var lavere i feltstudier spesielt med hensyn på vekking, ble det antatt at det foregår en tilvenning til støy under søvn.…”
Section: Virkninger På Søvnunclassified
“…It also determined that out of 930 subject nights, the average spontaneous (not noise-related) awakenings per night was 2.07 compared to the average number of noise-related awakenings per night of 0.24 (Fidell et al 1994). Additionally, a 1995 analysis of sleep disturbance studies conducted both in the laboratory environment and in the field (in the sleeping quarters of homes) showed that when measuring awakening to noise, a 10 dB increase in SEL was associated with only an 8 percent increase in the probability of awakening in the laboratory studies, but only a 1 percent increase in the field (Pearsons et al 1995). Pearsons et al (1995) reports that even SEL values as high as 85 dB produced no awakenings or arousals in at least one study.…”
Section: Affected Environment and Environmental Consequences: Airspacmentioning
confidence: 99%
“…Additionally, a 1995 analysis of sleep disturbance studies conducted both in the laboratory environment and in the field (in the sleeping quarters of homes) showed that when measuring awakening to noise, a 10 dB increase in SEL was associated with only an 8 percent increase in the probability of awakening in the laboratory studies, but only a 1 percent increase in the field (Pearsons et al 1995). Pearsons et al (1995) reports that even SEL values as high as 85 dB produced no awakenings or arousals in at least one study. This observation suggests a strong influence of habituation on susceptibility to noise-induced sleep disturbance.…”
Section: Affected Environment and Environmental Consequences: Airspacmentioning
confidence: 99%